Computer supported collaborative learning (CSCL) via social networking in mathematics - Guandasami, Wasugi (2013)
This research were designed to identify students’ interest towards computer supported learning process for mathematics lesson, students interest on the use of Geogebra in mathematics lesson and students’ perception on collaborative learning through social networking. This study deploys mixed method which is a combination of quantitative (Questionnaire) and qualitative (interviews) approach where students were taught transformation topic with the aid of Geogebra software and allowed to interact through social networking site (Facebook) to complete the activities given. 30 of Form two students were involved in the quantitative study who give their response to the questionnaire while five students were selected for qualitative study who participate in the interview session. Results of mean analysis showed that students perceived high level of interest towards computer supported learning process for mathematics lesson with M=4.56. Besides that, students also perceived high level of interest on the use of Geogebra in mathematics lesson with M=4.40. Lastly, students have a positive perception on collaborative learning through social networking with M=4.55. Results from the qualitative study also support the findings of quantitative study which the students stated that Geogebra software is very helpful in learning mathematics and very effective in cascading complex matters through easier method. In terms of collaborative learning, Facebook is an effective collaborative learning medium.which enables easier communication and effective idea sharing session. The study shows that students have displayed positive attitude towards mathematics lesson with the use of Geogebra software and social networking site.